DIGITAL TRANSFORMATION OF THE BANKING SECTOR: STRATEGIC ASPECTS OF HUMAN CAPITAL MANAGEMENT - Бабенко, Максим; Литвиненко, Аліна; Литвиненко, Олена; Новікова, Тетяна (SWorldJournal, 2025)
The article explores the strategic aspects of digital transformation in the banking sector, emphasizing its impact on human capital management. Digitalization is considered not only as the introduction of advanced technologies but also as a comprehensive